KEKUASAAN DISKRESI HAKIM PENGADILAN HUBUNGAN INDUSTRIAL - Widiastiani, Nindry Sulistya (Veritas et Justitia, 2021)
In this article the author discusses the discretionary powers granted to Labour Dispute Court judges. Better known, in comparison, are the discretionary powers of criminal court judges in determining penal sanctions or of Islamic court judges when granting dispensation to marry for underage couples. Using a juridical normative method, the discussion focusses on the principles underlying the Labour Dispute Court judge’ discretionary powers and its implementation.  The analysis shows that Labour Dispute Court judges do have and enjoy discretionary powers in determining betterment of working conditions, how to best fill gaps or seek clarity in the face of ambiguous rules and regulations found in work contract, company regulations or collective work agreement.